RELATIONSHIPS BETWEEN FAMILY AND WORK SATISFACTION: MODULATORY VARIABLES - Sánchez López, Mª Pilar; Quiroga Estévez, Mª Angeles (Anales de Psicología / Annals of Psychology)
Satisfaction, normaly defined as the cognitive component of subjective welfare, sums up the individual’s quality of life and is closely related to other variables such as selfesteem, depression, locus of control, etc. Traditionally, subjects consider that family and work are the most important realms for explaining their global satisfaction. But research on this subject has centred on separate analysis of each possible influence without considering the relationships that may occur between them. Futhermore, family and work have been considered as separate unrelated entities. Our present work (which forms part of a wider research project) centres on the simultaneous study of the possible influences exerted by different variables on satisfaction, both family and work satisfaction, and of the relationship between the two. The data, obtained from a group of 96 persons, paired and belonging to the three types of pairs evaluated (Traditional, Dual-Income and Dual-Career) reflect differential trends in the relationship between family and work satisfaction, on the basis of sex, age and whether they have children or not (the other aspects considered do not significantly modulate the relationship between satisfaction in both areas). Possible explanations for these data are offered as well as the lines of research to be followed henceforth as a continuation of the work presented).